Penggunaan Flashcard Sistem Periodik Unsur Terhadap Keterampilan Proses Sains Dasar Peserta Didik Kelas X SMA - Elsa Sriwahyuni (Orbital: Jurnal Pendidikan Kimia, 2022)
One component that is the goal of learning chemistry is science process skills. The view of chemistry teachers so far is that science process skills can be developed if learning applies practical or experimental methods. In fact, science process skills can be developed through learning activities that utilize learning media. This study aims to analyze the effect of the use of instructional media, namely elemental periodic system flashcards, on the science process skills of class X high school students. The research method used was a quasi-experimental method with a post-test only control group design. The sample in this study were 57 students of class X SMA who were divided into two classes, namely one experimental class and one control class. This research was conducted at SMA N 1 Kasihan, Kab. Bantul, Special Region of Yogyakarta. The results showed a p-value of 0.014 from the t-test data analysis of the science process skills of the control class and the experimental class. It can be concluded that there is a significant difference in science process skills between the experimental class that uses flashcard periodic system of elements compared to the control class.